Effect of circumferential static pressure nonuniformity caused by volute on tip leakage flow in a centrifugal compressor. (November 2019) - Fu, Li; Yang, Ce; Bao, Wenrui; Zhang, Hanzhi; Yang, Changmao; Li, Yanzhao
For a centrifugal compressor with volute, the flow field is circumferentially nonuniform because of the volute asymmetrical structure and leads to a circumferential difference in the tip leakage flow. In this work, the compressor performance and the casing wall static pressure distribution are measured, and the results are compared with the time-averaged results of the unsteady calculation to verify the reliability of the simulation. The results show a relationship between the tip leakage vortex trajectory and the high static pressure region in the diffuser, based on which a prediction model is established for the reverse propagation of pressure waves caused by a volute tongue. Influenced by the volute asymmetric structure, the trajectory, shape, and strength of the tip leakage vortex at different circumferential positions differs significantly. The tip leakage vortex trajectory affected by the high static pressure is more inclined to a circumferential direction because the tip leakage flow velocity flowing out of the suction surface is reduced, and the tip leakage flow with low velocity is subjected to the high-pressure gradient in a passage. Moreover, the tip leakage vortex breakdown in different passages differs significantly. A tip leakage vortex core more inclined towards the streamwise direction is more likely to break down than a tip leakage vortex core inclined towards the circumferential direction because of the larger reverse pressure gradient.